Front Matter Vol. 2, No. 2 December 2022 (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2022)
Uktub Journal Cover Editorial Team Editor's Address List of Contents